Overlap in Patient with Functional Dyspepsia and Unspecified Functional Anorectal Pain - Suharjo B Cahyono; Neneng Ratnasari; Siti Nurdjanah (Acta Interna The Journal of Internal Medicine, 2016)
Functional gastrointestinal disorders (FIGD) represent a common and important class of disorders within gastroenterology. FIGD are a cause of great anxiety, distress and morbidity. FIGD disorders maybe manifest as overlapping syndrome. Patients with functional dyspepsia (FD) show frequent overlapping of other gastrointestinal disease, such as functional anorectal pain. These overlap patients have more frequent or more severe symptoms, poor health related quality of life and higher somatization scores, and they are more likely to experience anxiety, depression or insomnia compared to non-overlap patients. These disorders were diagnosed according Rome III criteria and excluded structural diseases. Multimodalities approach should be used during treatment patient with FGID. It was reported a male patient with functional dyspepsia and unspecified functional anorectal pain overlap. Keywords: Functional gastrointestinal disorders, functional dyspepsia, functional anorectal pain